THE USE OF COUNTER–INTELLIGENCE OPERATION STRATEGY IN COPING WITH CYBER THREATS - Suratman, Yosua Praditya (Jurnal Pertahanan dan Bela Negara, 2017)
Abstract - The increasing number of cyberattacks that occur today indicates that Indonesia is an easy target for crime actors in the cyber world. Cyberattacks are selected because they are far more effective than conventional attacks - the military, and the actors are also invisible. Not to mention, the capacity of cyber handling, both infrastructure, funds, and human resources in Indonesia is inversely proportional compared to the number of cyberattacks in the last decade. Intelligence strategies, primarily counter-intelligence, is the answer to deter and detect the attacks, while the government fixing the regulations and policies of national cyber threats. Keywords: cyber, counter intelligence, security